Strategic Analysis of Cherat Packaging Limited A Case Study of one of the Key Players in Pakistan’s Packaging Industry - Haider, Syed Yashfeen; Ali, Sheikh Muhammad; Aleem, Dr. Muhammad Usman; Abbas, Mehdi; Faraz, Muhammad; Shamsi, Dr. Amir Feroz (The journal of contemporary issues in business and government, 2021)
Cherat Packaging Limited, a well-known name and one of the key players of cement packaging in Pakistan with an established market share, has recorded extensive expansion and diversification over the years. This case study is about Cherat Packaging Limited aims to examine this prominent company strategically, while paving way for future strategic developments, by giving the readers a comprehensive view of the company‟s vision, mission, key policies and principles, culture, financial performance, internal and external environments, challenges and growth opportunities.Even Cherat Packaging Limited, apparently one of the market leaders in the packaging industry, senses a need for continuous improvement to remain sustainable in the longer run, given the competitive, fast-paced, technology-driven and ever- changing business environment.